THE USE OF COMBINING DIALOGICAL THINKING AND HIGHLIGHTING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT - Salmon James Hukom (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2018)
As a receptive skill, reading plays important role since it helps the readers to enhance their knowledge and also entertain them in their leisure time. In comprehending the text, foreign readers including EFL learners always face problems. Besides lack of vocabulary has become major problem, the strategy that use by teachers in teaching reading is sometimes monotonous. Other reason is that the strategy is not appropriate with the kind of text. In teaching narrative, for example, the teachers should select suitable strategy which can be used by students to comprehend that text easily. In this article, the writer wants to introduce the use of combination Dialogical Thinking and Highlighting strategy in teaching narrative text. In Dialogical Thinking, students learn to reflect and think critically about central story issue, while Highlighting gives students opportunities to mark important ideas in reading. This combination is worthy since it attracts students’ attention to the very specific information in reading passage. Moreover, the students are easy to find the answers for certain kind of questions.